Dissecting the curriculum for Deaf student teachers at a Teacher Training College in Rwanda - James Maizere (International Journal of Studies in Inclusive Education)
Curriculum is a key aspect of teaching and learning for students. Central to the curriculum may be its clarity on its components and ability to address the needs of all students. A good curriculum must be explicit on its components, like resources or time. This study aimed to dissect the curriculum for a Teacher Training College (TTC) that included Deaf student teachers in all its teaching and learning processes. This study used an interpretive paradigm to allow the participants to provide their subjective views on the subject. It adopted a qualitative approach and used a narrative research design. One TTC administrator, tutor, and two Deaf student teachers were selected for this study. This study found that the National Examinations and School Inspection Authority assessed the Deaf student teachers before the TTC enrolled them. Still, no one was sure about the nature of the assessments. The study also found that The Deaf student teachers learned the same curriculum as the hearing student teachers with no formal adjustments. This study further found that TTC lacked the resources to implement inclusion successfully. The study recommended that the National Examinations and School Inspection Authority conduct audiometric assessments of prospective Deaf before enrolling. Moreover, the study suggested that the Rwanda Basic Education Board (REB) employ skilled tutors in Deaf studies who could adjust the TTC curriculum.